ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI DEEP BACK MASSAGE UNTUK MENGURANGI NYERI PERSALINAN KALA I FASE AKTIF DI PUSKESMAS CINERE - Karina Oktaviyadi (2023)
Childbirth is the process of removing the baby from the uterus through the birth canal. The process begins with uterine contractions, which cause the uterus to enlarge and thin the cervix, this process certainly causes pain felt by the mother. The purpose of this study was to analyze Deep Back Massage therapy interventions to reduce labor pain during the first stage of the active phase. This study used a quasi-experimental research design with 2 patients and pain intensity was measured using the Numeric Rating Scale (NRS) which consisted of a scale of 0 (no pain) to a scale of 10 (severe pain). The results of this study proved that Deep Back Massage therapy can reduce the level or severity of pain felt by both patients and make patients feel relaxed and comfortable. The results of the evaluation after deep back massage intervention were carried out 4 times in managed patients, the results showed that there was a decrease in pain in the range of 4-6 (moderate pain). Whereas in patients the resume is in the range of 3-5 (mild-moderate pain). It is recommended that health workers and mothers who are about to give birth use Deep Back Massage therapy to be used as a complementary therapy that can reduce pain.